Effect of landscape modification on primate assemblages of the Magdalena River Valley, Colombia - Néstor Roncancio-Duque (Caldasia)
Population and community dynamics are affected by local landscape disturbances, and the answer of each species to these changes could differentially affect species survival. Natural land cover in the Magdalena River valley, Colombia, has been reduced by almost 70 % and fragmented. There inhabit isolated and reduced populations of Alouatta seniculus, Ateles hybridus, Cebus versicolor, and Sagui-nus leucopus (Primates). To understand the effect of fragmentation over these species, the relationship between altitude, landscape and class metrics, and plant structure and diversity with the population density of these four primates in 20 localities were assessed. Additionally, the relationship between the density of A. hybridus, assumed as a better competitor, and the density of the other primates was assessed. Mean shape index was the most related variable and affected positively the density of A. hy-bridus, C. versicolor, and S. leucopus and negatively that of A. seniculus. Weight class index was the second more important variable, the four primates increased their density where more mature is the plant cover. Diameter at breast height was positively related with the density of A. hybridus and C. ver-sicolor, negatively related for A. seniculus and not related to S. leucopus density. Tree density was re-lated negatively with the density of A. seniculus and positively with S. leucopus.A. hybridus was related to the density of the other primates, positively to A. seniculus and negatively to the other two species.